2017
DOI: 10.1051/epjconf/201714010001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of shear bands formation in a granular material

Abstract: Abstract. We present an experimental investigation of the formation of shear bands in a granular sample submitted to a biaxial test. Our principal result is the direct observation of the bifurcation at the origin of the localization process in the material. At the bifurcation, the shear band is spatially extended: we observe a breaking of symmetry without any sudden localization of the deformation in a narrow band. Our work thus allows to clearly distinguish different phenomena: bifurcation which is a ponctual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Bardet and Proubet (1991) believed that the inclination angle of shear band to the minor principal stress increases with axial strain in numerical modelling of triaxial tests in plane strain condition (also known as biaxial tests) while Kuhn (1999) found the opposite. Gu et al (2014) and Jiang and Zhang (2015) reported that shear band thickness increased with axial strain, which is different from Bardet and Proubet (1991) and Nguyen et al (2017). These inconsistencies reflect the complexity of the problem, indicating formation of shear band and evolution mechanism need further investigation.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Bardet and Proubet (1991) believed that the inclination angle of shear band to the minor principal stress increases with axial strain in numerical modelling of triaxial tests in plane strain condition (also known as biaxial tests) while Kuhn (1999) found the opposite. Gu et al (2014) and Jiang and Zhang (2015) reported that shear band thickness increased with axial strain, which is different from Bardet and Proubet (1991) and Nguyen et al (2017). These inconsistencies reflect the complexity of the problem, indicating formation of shear band and evolution mechanism need further investigation.…”
Section: Introductionmentioning
confidence: 86%
“…Among the current available studies, Harris et al (1995), Finno et al (1997) and Desrues and Viggiani (2004) examined the factors on shear band formation using the stereophotogrammetry technique. Nguyen et al (2017) adopted a digital image analysis tool and showed the formation of shear band involves three stages. Zheng et al (2019) applied photo-elastic technique to observe particle scale responses inside shear band.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations